2014
DOI: 10.1111/evj.12262
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of palmar/plantar digital neurectomy in horses with foot pain evaluated with magnetic resonance imaging: 50 cases (2005–2011)

Abstract: Palmar/plantar digital neurectomy can improve or resolve lameness in horses with foot pain unresponsive to medical therapy without serious post operative complications. However, horses with core or linear lesions of the DDFT should not be subjected to PDN as these horses experience residual lameness or early recurrent lameness after surgery. Magnetic resonance imaging can be used to identify these horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
(33 reference statements)
0
26
4
Order By: Relevance
“…Different factors, such as horse occupation, lameness duration, and injury type, among others, have been reported to affect the prognosis for certain foot injuries 6,8,10‐15 . A previous study of mainly Warmblood horses found an association between chronic lameness and deep digital flexor (DDF) tendinopathy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Different factors, such as horse occupation, lameness duration, and injury type, among others, have been reported to affect the prognosis for certain foot injuries 6,8,10‐15 . A previous study of mainly Warmblood horses found an association between chronic lameness and deep digital flexor (DDF) tendinopathy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…; Gutierrez‐Nibeyro et al . ). Although catastrophic complications are not common, severe and potentially fatal outcomes such as DDFT rupture can occur and should be considered prior to electing the procedure (Jackman et al .…”
Section: Specific Conditionsmentioning
confidence: 97%
“…Moderate to severe DDFT injuries are generally a contraindication for palmar neurectomies, both as the risk of progressive injury and even rupture is higher and horses with more advanced DDFT lesions have been reported to have a less successful outcome in eliminating lameness (Gutierrez‐Nibeyro et al . ). Conversely, horses with injuries primarily affecting the navicular bone can have a good outcome following this surgery.…”
Section: Specific Conditionsmentioning
confidence: 97%
“…; Mair and Kinns ), abnormal conformation (Schramme ) and previous neurectomy of the palmar digital nerves (Gutierrez‐Nibeyro et al . ).…”
Section: Introductionmentioning
confidence: 97%